Study of Anthocyanin Molecule Blocking as Anti-Hypertensive through the Pathway of the Renin-Angiotensin-Aldosterone System (RAAS) - Budiarto, Dwi; Wijianto, Bambang; IH, Hariyanto (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2023)
Anthocyanins are flavonoid-derived compounds that can reduce blood pressure. This study aims to determine the affinity value of the compound to bind to Angiotensin Converting Enzyme (ACE) and bind to Angiotensin II type 1 Receptor (AT1R) and to determine the distance and shape of the bond that occurs. The results of anthocyanin-derived compounds Delphinidin, Petunidin, Malvidin, Cyanidin, Peonidin, and Pelargonidin have anti-hypertensive potential through the Renin Angiotensin Aldosterone (RAAS) pathway based on molecular docking calculations. The affinity value of each, against Angiotensin Converting Enzyme (ACE) -7.7; -7.8; -7.7; -7.7; -7.8, and -7.7, the best affinity value in anthocyanin-derived compounds is shown in the Malvidin test compound which has three types of hydrogen bonds at a distance of ± 2 Å (ASP377, TYR520, ASP415) and has 1 type of bond that is the same as the lisinopril control (TYR520). While the affinity value to Angiotensin Receptor (AT1R) is -7.7; -7.7; -7.8; -7.7; -7.8, and -7.6, respectively, the best affinity value is shown in the Malvidin test ligand compound of -7.8 kcal/mol which has four types of hydrogen bonds ± 2 Å distance (TYR92, SER105, ARG167, TRP84) and has one kind of bond in common with lisinopril control (TYR520).